Cadmium levels in human breast tissue and estradiol serum levels: Is there a connection? - Buha Djordjevic, Aleksandra; Andjelković, Milena; Kačavenda, Elena; Javorac, Dragana; Antonijević Miljaković, Evica; Marić, Djurdjica; Baralić, Katarina; Djukić-Ćosić, Danijela; Ćurčić, Marijana; Antonijević, Biljana; Bulat, Zorica (Archives of Pharmacy, 2021)
Cadmium (Cd), one of the most abundant environmental pollutants, is considered to have endocrine disrupting properties. However, data on the dose-response relationship between Cd dose and levels of hormones have been insufficiently studied, especially in human data sets. Thus, the aim of this study was to determine the possibility of analyzing data obtained from a case-control study in female patients with benign/malignant breast tumors, using the Benchmark dose (BMD) concept. The collected data on Cd levels in breast tissue and estrogen serum levels were processed in PROAST software using different variables. The dose-response relationship between the internal dose of Cd and estradiol levels in the serum was investigated and BMD intervals were calculated. The dose-response relationship between the Cd concentration in breast tissue and the estradiol serum level was shown, indicating lower estradiol serum levels as a consequence of higher Cd concentrations in breast tissue. As one of the few studies analyzing human data using the BMD approach, these findings could have a pivotal role in dose response analysis of data collected from human studies.
Keywords: Endocrine disruption; cadmium; BMD concept; PROAST software; human studies